Effect of Phosphor Layer Size on the Optical and Thermal Properties of Chip Scale Packaged Light-Emitting Diodes. (9th April 2018) - Bak, Gyu Hyeong; Oh, Sun Woo; Sung, Hyun Ho; Yoon, Suk Bum; Kim, Won Jung; Jeong, Hwan-Hee; Song, June-O; Seong, Tae-Yeon
Abstract : We investigated the effect of phosphor film thickness and width on the optical and thermal properties of the chip scale package (CSP) LEDs. Eight different types of phosphor-converted white CSP LEDs with normal performance (colour rendering index (CRI) > 70, CCT 5700 K) were prepared by using mixed multicolor phosphors. For five samples, whose CSP area was fixed at 1.8 x 1.8 mm 2, the thickness of the phosphor layers was varied from 100 to 500 μm at intervals of 100 μm. For other three samples where the phosphor layer thickness was fixed at 300 μm, the CSPs had three different areas of 1.6 x 1.6, 1.8 x 1.8, and 2.0 x 2.0 mm 2 . It was shown that as the thickness of the phosphor film increased, the luminous flux and the radiation angle increased. On the other hand, as the CSP area increased, the luminous flux remained somewhat unchanged, while the radiation angle decreased. This could be attributed to the fact that CSP did not have a reflector (namely, a housing material) and so the blue light of the chip did not excite the whole area of the phosphor. Furthermore, a junction temperature measurement system was used to characterize the junction temperatures of the five different samples whose phosphor layer thicknesses were varied from 100 to 500 μm. At high forward current, the junction temperature increased with increasing phosphor film thickness.